2016
DOI: 10.1186/s12887-016-0609-7
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of component-resolved diagnostics in peanut allergy in children attending a Regional Paediatric Allergology Clinic

Abstract: BackgroundTo date, diagnosing food allergies in children still presents a diagnostic dilemma, leading to uncertainty concerning the definite diagnosis of peanut allergy, as well as to the need for strict diets and the potential need for adrenalin auto-injectors. This uncertainty in particular is thought to contribute to a lower quality of life. In the diagnostic process double-blind food challenges are considered the gold standard, but they are time-consuming as well as potentially hazardous. Other diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 23 publications
3
28
0
Order By: Relevance
“…It has been reported earlier 15,26 and now confirmed in the present study that the ratio of peanut-specific, and in particular of Ara h 2specific IgG 4 over IgE antibody levels is higher in subjects that tolerate peanuts than in those that are allergic to peanuts. In several In line with some earlier publications 6,9,12,[15][16][17] but opposite to some others, 2,7,18,19 our study found clear support for an association between sensitization to Ara h 2 and symptom severity during challenge. Conflicting results in very similarly designed studies such as the study by Blumchen et al 18 and the present study may perhaps be explained by differences in stop-criteria during challenge.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…It has been reported earlier 15,26 and now confirmed in the present study that the ratio of peanut-specific, and in particular of Ara h 2specific IgG 4 over IgE antibody levels is higher in subjects that tolerate peanuts than in those that are allergic to peanuts. In several In line with some earlier publications 6,9,12,[15][16][17] but opposite to some others, 2,7,18,19 our study found clear support for an association between sensitization to Ara h 2 and symptom severity during challenge. Conflicting results in very similarly designed studies such as the study by Blumchen et al 18 and the present study may perhaps be explained by differences in stop-criteria during challenge.…”
Section: Discussionsupporting
confidence: 72%
“…Traditionally, serum IgE tests like ImmunoCAP measure IgE against whole peanut extract. 2,7,18,19 Not only IgE against peanut extract but also against Ara h 2 can be found in peanut-tolerant subjects. In multiple studies, IgE to Ara h 2 has been reported to perform better than extract in discriminating peanut allergic patients from tolerant sensitized subjects, both in children 2-8 and adults.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of anti-IgE has been shown to lead to a reduction of hospitalization in both severe asthma and children with inner city asthma with fall exacerbations (6). For food allergy, the use of component testing has suggested which patients might be at risk for anaphylaxis to food (7). It is possible to envision the use of phenotypes as an aid in personalizing the selection of a therapeutic option and giving us guidance in predicting the natural history of a patient with EoE.…”
mentioning
confidence: 99%